Examining the experiences of student veterans on campus : a phenomenological qualitative study - Legreid, Jansen S. (University of Wisconsin--Whitewater, 2020)
Student veterans represent a rising proportion of university students due to the increased utilization of state and federal education benefits. However, few studies have examined the daily experiences of these individuals following combat operations in Iraq and Afghanistan and how these experiences may influence the success of these individuals on civilian campuses. The current study includes individual interviews with four student veterans from the University of Wisconsin - Whitewater. To better understand student veteran experiences and identify factors that increase or decrease academic and transition success, I utilized a phenomenological framework. The findings reveal that student veterans: have unique perspectives due to differing values from their civilian peers, have needs influenced by various converging identities and roles, and experience a continuum of connectedness with peers and faculty. Additionally, limitations of the current study are addressed and suggestions for future research with this population are presented.
This file was last viewed in Adobe Acrobat Pro.
Keywords: Veterans--Education; College campuses